Consensus guidelines for the management of pineal region tumours for low- and middle-income countries - Saqib Kamran Bakhshi; Naureen Mushtaq; Rabeet Tariq; Moeez Tariq; Asim Hafiz; Ahmed Gilani; Hafiza Fatima Aziz; Muhammad Shahzad Shamim; Altaf Ali Laghari; Kaynat Siddiqui; et al. (Journal of the Pakistan Medical Association, 2024)
Pineal region tumours are rare and mainly arise at ayounger age. They can be categorized into various types:germ cell tumours (GCT), pineal parenchymal tumours(PPT), meningiomas, gliomas, pineoblastoma, pinealparenchymal tumours of intermediate differentiation,papillary tumours of the pineal region, and SMARCB1-mutant desmoplastic myxoid tumour. Within GCT,germinomas are the most prevalent, comprising themajority of tumours in this region, while nongerminomatousGCTs are also present. In rare instances,metastases from other sites may manifest. These tumoursoften lead to obstructive hydrocephalus and commonlyexhibit symptoms related to mass effect, includingheadache, nausea, vomiting, and impaired gait stability.Different subtypes of pineal region tumours exhibitdistinct radiological characteristics, thus imaging remainsthe primary diagnostic tool. Histologic diagnosisnecessitates biopsy, unless in cases of germ cell tumours,particularly germinomas, which can be identified throughelevated levels of tumour markers like alpha-fetoprotein(AFP) and human chorionic gonadotropin (HCG) in bothcerebrospinal fluid (CSF) and serum. While benigntumours might be effectively treated with radicalresection alone, malignant tumours demand additionalchemotherapy and radiotherapy following surgicalremoval. Keywords: Pinealoma, alpha-fetoproteins,meningioma, germinoma, chorionic, gonadotropin,hydrocephalus, headache, vomiting, glioma, biopsy,nausea, gait, tumours.